The Facial Soft Tissue Effects of Orthognathic Surgery - Gill, Daljit S.; Lloyd, Timothy; East, Charles; Naini, Farhad B. (Facial Plastic Surgery, 2017)
Orthognathic surgery is undertaken to correct anteroposterior, vertical, and transverse anomalies of the maxilla and mandible. Surgery has significant effects on the overlying soft tissue envelope. Some of these effects are beneficial while others may be detrimental to facial aesthetics. This review aims to update the reader on what soft tissue changes occur following orthognathic surgery to the mandible and maxilla. It is important to anticipate the detrimental effects of orthognathic surgery as this will allow the patient to be warned about them before treatment and in some cases, adjunctive procedures may be planned to limit the unwanted changes.
Keywords: orthognathic surgery; maxillary advancement; maxillary impaction; mandibular advancement; mandibular setback; genioplasty; soft tissues